Planning for wastewater reuse - Fresa F.; Melli F.; Piccinni A.F.; Santandrea V.; Specchio V. (Water saving in Mediterranean agriculture and future research needs [Vol. 2], 2007)
This paper presents the results of a research work aimed at defining useful criteria for planning treated wastewater reuse. All the possible forms of reuse are preliminarily analysed, supplementary treatments required for different uses are identified according to reclaimed water characteristics and the additional costs required to adjust the treatment plants to the reuse purposes are estimated; the implications related both to the organizational and management problems of the treatment-reclamation system and to the methodological and technical aspects relative to water-pricing policies are also analysed.
Proceedings of the International Conference WASAMED Project (EU contract ICA3-CT-2002-10013), 2007/02/14-17, Valenzano (Italy)